Health information needs, source preferences and engagement behaviours of women with metastatic breast cancer across the care continuum: protocol for a scoping review. Issue 2 (17th February 2017) - Tucker, Carol A; Martin, M Pilar; Jones, Ray B
Abstract : Introduction: The health information needs, information source preferences and engagement behaviours of women with metastatic breast cancer (mBC) depend on personal characteristics such as education level, prior knowledge, clinical complications, comorbidities and where they are in the cancer journey. A thorough understanding of the information behaviours of women living with mBC is essential to the provision of optimal care. A preliminary literature review suggests that there is little research on this topic, but that there may be lessons from a slightly broader literature. This review will identify what is known and what is not known about the health information needs, acquisition and influences of women with mBC across the care continuum. Findings will help to identify research needs and specific areas where in-depth systematic reviews may be feasible, as well as inform evidence-based interventions to address the health information needs of female patients with mBC with different demographics and characteristics and across the mBC journey. Methods and analysis: A scoping review will be performed using the guidelines of Arksey and O'Malley as updated by subsequent authors to systematically search scientific and grey literature for articles in English that discuss the health information needs, source preferences, engagement styles, and associated personal and medical attributes of women ≥18 years living with mBC at different stages of the disease course. A variety of databases (including Cumulative Index to Nursing and Allied Health Literature (CINAHL), PubMed, Excerpta Medica Database (EMBASE), Academic Search Premier, Cochrane Database of Systematic Reviews, PsycINFO, Health Source: Nursing/Academic Edition, and PQDT Open), oncology, patient advocacy and governmental websites will be searched from inception to present day. Research and non-research literature will be included; no study designs will be excluded. The six-stage Arksey and O'Malley scoping review methodological framework involves: (1) identifying the research question; (2) searching for relevant studies; (3) selecting studies; (4) charting the data; (5) collating, summarising and reporting the results; and (6) consulting with stakeholders to inform or validate study findings (optional). Data will be extracted and analysed using a thematic chart and descriptive content analysis. Ethics and dissemination: Being a secondary analysis, this research will not require ethics approval. Results will be disseminated through patient support organisations and websites and publications targeting healthcare professionals, advocates and patients.